Characteristics, ethiology and assessment of sexual offending in persons with intellectual disability - Tomić, Katarina (Specijalna edukacija i rehabilitacija, 2017)
The paper presents an overview of the studies dealing with the etiology, types and clinical expression of sexual offending in people with intellectual disability, with a brief overview of some of the methods and techniques of structured assessment of deviant sexual behavior. A review of possible etiological factors provides an overview of the static and dynamic risks factors of sexual offending and recidivism. The results indicate an increased incidence of sexual offending in people with intellectual disabilitiy compared to those of a typical development. The most important risk factors for the manifestation of deviant sexual behavior include: early victimization, misunderstanding of social rules and restrictions, poor impulse inhibition, behavioral and emotional disregulation and some neurobiological factors associated with genetic syndromes. People with intellectual disabilities usually choose other people with disabilities, as well as children, for victims of sexual offenses. The results of the presented research point to the importance of continuous sexual education of people with intellectual disabilitiy and preventive action in order to mitigate the well known risk factors for expressing sexually deviant behavior.